اللغة العربية وأهميتها في فهم القرآن والسنة - zulfikri muhammad (Imtiyaz : Jurnal Pendidikan dan Bahasa Arab, 2019)
Abstract Learning Arabic is a necessity because we are helped with it to know this religion better. The sources of our religious law speak Arabic, and the poles of the turats are a reference in explaining the purposes of this religious teaching, all of them speak Arabic. Ibnu Taimiyyah said, Arabic is part of religion, and knowing it is an obligation. Because, understanding the Qur'an and the Sunnah is obligatory, while the two will not be understood without knowing Arabic. Something that is not perfect is an obligation but with it, then he too becomes obligatory.